2001
DOI: 10.1079/phn200064
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the health status of migrants in France, in relation to their dietary practices

Abstract: Objective: To review studies on the morbidity, mortality and nutrition of migrant populations in France. Design: A systematic search of the bibliographic database Medline, and direct contact with associations and institutions concerned with migrants' health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
86
2
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 47 publications
7
86
2
7
Order By: Relevance
“…In accordance with our results, earlier studies showed higher consumption of starchy foods among North African migrants in France compared with local-born French (Darmon and Khlat, 2001). In contrast, unlike our findings for fruits and vegetables, other studies indicated that North African migrants conserved a traditionally high consumption of this food group (Darmon and Khlat, 2001;Mejean et al, 2007).…”
Section: 00supporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with our results, earlier studies showed higher consumption of starchy foods among North African migrants in France compared with local-born French (Darmon and Khlat, 2001). In contrast, unlike our findings for fruits and vegetables, other studies indicated that North African migrants conserved a traditionally high consumption of this food group (Darmon and Khlat, 2001;Mejean et al, 2007).…”
Section: 00supporting
confidence: 93%
“…In accordance with our results, earlier studies showed higher consumption of starchy foods among North African migrants in France compared with local-born French (Darmon and Khlat, 2001). In contrast, unlike our findings for fruits and vegetables, other studies indicated that North African migrants conserved a traditionally high consumption of this food group (Darmon and Khlat, 2001;Mejean et al, 2007). Contrary to studies in the general population, country of birth in this deprived population probably reflected economic barriers to food access rather than sociocultural characteristics, which help to maintain traditional healthy dietary patterns (Mejean et al, 2008).…”
Section: 00supporting
confidence: 93%
“…However, at this point it should be mentioned that the consumption of energy-rich food is considered beneficial by low rank people, when manual work is involved. Regarding alcohol drinking, several studies have reported an inverse relationship with SES (7,(23)(24)(25) . Alcohol intake was satisfactory in our study, but it was significantly different between SES groups, with the high education/low income group having the lowest consumption and the low education/high income group having the highest intake ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Ainsi, il a été montré qu'un fort capital social (repères culturels, tissu social et soutien social) limite le risque de mal s'alimenter alors que la vulnérabilité sociale (acculturation, isolement et dévalorisation de soi) l'augmente [86][87][88]. La pauvreté s'accompagne souvent de solitude, d'ennui et de dépres-sion, ce qui conduit à augmenter le temps passé devant la télévision.…”
Section: Facteurs Explicatifs Indirectsunclassified
“…En revanche, ceux qui ont un faible SSE, sont probablement plus nombreux à attendre leurs parents le soir devant la télévi-sion, en particulier s'ils habitent dans un quartier considéré comme potentiellement dangereux. Ainsi, bien que l'allongement du temps 18 [92] et [91] [87].…”
Section: Facteurs Explicatifs De L'augmentation Du Gradient Social Deunclassified